A Simple Method for Determining Surface Porosity Based on SEM Images Using OriginPro Software - Mikrajuddin Abdullah; Khairurrijal Khairurrijal (Indonesian Journal of Physics, 2009)
We proposed a simple method for predicting surface porosity of materials based on scanning electron micrograph (SEM) images. The porosity was determined by calculating volume beneath the surface and volume beneath a flat surface, the height of which is equal to maximum height of any point on the sample’s surface. The SEM image was firstly converted into two-dimensional matrix of gray scale and all procedures were performed using instructions provided by OriginPro software. The predicted results were in good agreements with direct calculation and measurement of the samples porosities.